Stealth-Maneuver Generation for Non-Stealth Aircraft: A Control Barrier Function Approach - Mustafa Demir; Ege C. Altunkaya; Akın Çatak; Fatih Erol; Emre Koyuncu; İbrahim Özkol; Uğur Zengin (Aerospace)
Aiming to address the vulnerability of non-stealth aircraft to radar detection due to inherent design limitations, this paper proposes a method to generate maneuvers that reduce an aircraft’s radar cross-section (RCS) value below a specified threshold. The proposed method employs control barrier functions and leverages the relationship between control inputs and the RCS. Due to confidentiality concerns, the required RCS database for the F-16 aircraft was generated through analyses performed using the created geometry. The results are compared with a virtual path that excludes RCS constraints and does not alter the aircraft’s attitude. Simulations reveal that <semantics>89.6%</semantics> of the cases using the proposed method achieve a mean RCS value below the threshold, compared to only <semantics>1.26%</semantics> for the virtual path. Moreover, the ratio of the time during which the RCS constraint is successfully met to the total simulation time averages over <semantics>78%</semantics> across all simulations, demonstrating the method’s effectiveness in reducing the RCS value below the specified threshold.